Analysis of the Performance Management System and its Application to Company Employees - Amrin Nasution; Eka Dewi Setia Tarigan; Patar Marbun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This Research Aims To Describe How The Implementation Of An Employee Performance Management System At PT. Bangun Niaga Company In Medan Municipality. The type of research used in this study is qualitative with 55 respondents. Data Collection Techniques Are Done Through Observations And Interviews. Technical Data Analysis Namely Qualitative Descriptive Analysis Expressed In The Forms Of Questions, Responses And Interpretations Obtained From Observations And Direct Interviews. The results of this study show that in general it has not run effectively. This can be seen from the indicators (A) Commitment and Policies are running smoothly, (B) Planning is going well, (C) Implementation is running well, (D) Inhibiting factors are not running according to the indicators that have been set and (E) Factors Support Goes Well.